2020
DOI: 10.3390/molecules25020315
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tilmicosin Nanostructured Lipid Carriers for Improved Oral Delivery in Broilers: Physiochemical Characterization and Cellular Permeation

Abstract: This study aimed to develop nanostructured lipid carriers (NLCs) for improved oral absorption of tilmicosin (TMS) in broilers. Thus, palmitic acid, lauric acid, and stearic acid were selected as solid lipids to formulate TMS-pNLCs, TMS-lNLCs, and TMS-sNLCs, respectively. They showed similar physicochemical properties and meanwhile possessed excellent storage and gastrointestinal stability. The TMS interacted with the lipid matrix and was encapsulated efficiently in NLCs in an amorphous structure. NLCs could en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
1
7
1
Order By: Relevance
“…The absorption bands between 1100 and 1200 cm −1 were from ether and cyclic C‐C bonds in the ring structure of pectin molecules. For Til, the principal vibration absorption peaks are: O‐H at 3440 cm −1 , C‐H at 2940 cm −1 , C=O at 1750 cm −1 and 1690 cm −1 , C=C at 1580 cm −1 and C‐O at 1050 cm −1 29 . The presence of many components with O‐H functions could be the factor that increments the signal at 3250–3750 cm −1 in particles studies 2 .…”
Section: Resultsmentioning
confidence: 98%
“…The absorption bands between 1100 and 1200 cm −1 were from ether and cyclic C‐C bonds in the ring structure of pectin molecules. For Til, the principal vibration absorption peaks are: O‐H at 3440 cm −1 , C‐H at 2940 cm −1 , C=O at 1750 cm −1 and 1690 cm −1 , C=C at 1580 cm −1 and C‐O at 1050 cm −1 29 . The presence of many components with O‐H functions could be the factor that increments the signal at 3250–3750 cm −1 in particles studies 2 .…”
Section: Resultsmentioning
confidence: 98%
“… 24 In addition, TIM-loaded lipid nanocarriers prepared through the high shear method display excellent storage and gastrointestinal stability and consequently enhanced oral absorption in broilers. 3 , 4 Zhou et al found that TIM-loaded in alginate-chitosan nanogels shows stronger sustained drug release compared with the injection of pure TIM. 5 Although previous studies have achieved the successful encapsulation and protection of TIM, facile preparation of TIM-loaded polymeric NPs with well-controlled size and tunable properties and functions remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Sahito et al, also fabricated three types of tilmicosin-loaded NLCs to enhance the oral bioavailability of the drug [ 175 ]. NLCs were prepared by high shear and ultrasonic methods with palmitic acid, lauric acid, or stearic acid as a solid lipid, oleic acid as oil, and Tween 20 as a surfactant.…”
Section: Recently Developed Formulations To Bypass P-gp and Enhance Oral Bioavailability Of P-gp Substratesmentioning
confidence: 99%